Peranan Pemeriksaan CT Angiografi Thorax pada Kasus Hemoptisis - Amelia Anggia Putri; Dini Rachma Dini Rachma (RSUD Dr. Saiful Anwar Province of East Java, 2026)
Introduction: Haemoptysis is one of the most common clinical symptoms in tuberculosis (TB) patients, especially in chronic pulmonary TB cases. In Indonesia, as one of the countries with the highest prevalence of tuberculosis in the world, the incidence of haemoptysis in tuberculosis patients remains a challenge in clinical management and health care systems. Imaging of pulmonary arteries with CT angiography of the thorax compared to CT scan without contrast is an effective tool for evaluation and treatment of idiopathic and tuberculosis-induced haemoptysis. Case illustration: Case series of three patients with clinical symptoms of haemoptysis who underwent CT Angiography examination of the thorax at Saiful Anwar Hospital. Discussion: Case series of three patients with a history of haemoptysis found the source of bleeding from the bronchial arteries, where the underlying cause was Tuberculosis infection. Conclusion: three case series of patients with haemoptysis that gave a dilated and tortuous picture of the bronchial arteries. The importance of using CT angiography of the thorax in determining the location of the artery causing haemoptysis, may help the management of haemoptysis. Different arteries have different manifestations and management approaches.